Inspire but don't interfere: Managerial influence as a double‐edged sword for innovation. Issue 2 (10th June 2021) - Gerpott, Fabiola H.; Bledow, Ronald; Kühnel, Jana
Abstract: Managers play a pivotal role in the innovation process; yet, the mechanisms through which managers enhance or undermine innovation are not well understood. Drawing upon self‐concordance theory, we argue that managers can augment employees' self‐concordance—defined as the congruence of goals and actions with inner values and preferences—through transformational behavior and thereby contribute to innovation. However, transformational behavior is closely coupled to another form of influence, namely, process management, the attempt to directly manage innovation‐related activities. This form of managerial influence reduces employees' self‐concordance and thereby undermines innovation. We test our conceptual model in a sample of 188 innovation projects using a contextualized method that asked employees to assess their self‐concordance and their managers' behavior during each project. Managers evaluated for each project the innovativeness of the outcome. Multilevel path‐analysis provided support for our hypotheses. We discuss future research implications to disentangle innovation‐facilitating and innovation‐undermining facets of managerial influence.